Linking Innovation and Literacy to MSME Performance via Digital Marketing - Pasaribu, Dompak; Tambunan, Debora; Sinurat, Elperida Juniarni (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Digital marketing serves as a key factor in improving the performance of MSMEs. This study investigates the role of digital marketing as a mediating variable by assessing both the direct and indirect impacts of financial literacy and product innovation on MSME performance. Using a descriptive and quantitative research design, the study involved a sample of 250 MSME actors from a specific region. The data were analyzed using Structural Equation Modeling (SEM) based on the Partial Least Squares (PLS) method. The results show that financial literacy and product innovation each have a significant and positive effect on digital marketing. In turn, digital marketing, along with these two variables, plays a crucial role in enhancing MSME performance. Notably, the study finds that digital marketing acts as a full mediator in the relationship between financial literacy and product innovation with MSME performance. This indicates that improvements in financial knowledge and product development can significantly boost business outcomes when supported by effective digital marketing strategies. These findings highlight the importance of integrating financial literacy, innovation, and digital marketing to support MSME growth in the region studied.